1996
DOI: 10.1074/jbc.271.36.22159
|View full text |Cite
|
Sign up to set email alerts
|

Protein Splicing Involving the Saccharomyces cerevisiae VMA Intein

Abstract: Protein splicing involves the excision of an internal protein segment, the intein, from a precursor protein and the concomitant ligation of the flanking N-and Cterminal regions. It occurs in mesophilic bacteria, yeast, and thermophilic archaea. The ability to control protein splicing of a thermophilic intein by temperature and pH in a foreign protein context facilitated the study of the mechanism of protein splicing in thermophiles. On the other hand, no direct studies have been done on the mechanism of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 238 publications
(195 citation statements)
references
References 37 publications
6
180
0
6
Order By: Relevance
“…The proposed mechanism for the S. cerevisiae Vma intein is shown in Figure 3 (see refs. 24,25). Splicing is initiated by an N-S acyl shift that converts a peptide bond into a thioester at the N-extein junction site.…”
Section: Problem Under Investigationmentioning
confidence: 99%
“…The proposed mechanism for the S. cerevisiae Vma intein is shown in Figure 3 (see refs. 24,25). Splicing is initiated by an N-S acyl shift that converts a peptide bond into a thioester at the N-extein junction site.…”
Section: Problem Under Investigationmentioning
confidence: 99%
“…The third step of the splicing reaction yields two immediate products, the excised 50 kDa VDE with a C-terminal aminosuccinimide residue and the spliced MT polypeptide linked by a thioester bond. Though the rate of hydrolysis of the terminal succinimide residue has been determined as slow, the rate of rearrangement of thioester of the Cys455 residue by S→N acyl shift was proved to be much faster, with the equilibrium favouring the amide form, thus autocatalytically yielding a normal peptide bond (Chong et al 1996).…”
Section: Chemistry Of the Splicing Reactionmentioning
confidence: 99%
“…The chemical framework for protein splicing in the molecule of the VMA1 protein has been thoroughly explained (Chong et al 1996;Kawasaki et al 1996). However, the structural context which enables the exact splicing between the two reactive cysteine residues separated by 454 amino acids is still in question (see Fig.…”
Section: Structural Context Of Vde For the Splicing Reactionmentioning
confidence: 99%
“…In the papain family, highly conserved Asn is essential for catalysis, forming the Cys-His-Asn catalytic triad. The residues Cys, His, and Asn are also important for protein splicing: mutations of Cys 284 at the N-terminal splice site, His 736 , Asn 737 and Cys 738 at the C-terminal splice site result in defects of protein splicing [5][6][7][8][9][10]. The His 362 residue apart from the N-terminal splice site is also crucial for protein splicing [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, the 120 kDa nascent translation product of the VMA1 gene, termed Vmal protozyme [1], autocatalytically excises out the 50 kDa DNA endonuclease (VDE; FM^7-derived endonuclease, see [2]) and splices the two external polypeptides to form the 70 kDa catalytic subunit of the vacuolar H + -ATPase [3,4] Substitution of amino acids around the splice junctions has shown that the structure around the cleavage sites of the substrate is important for the splicing reaction [5][6][7][8][9][10]. Mutational analysis has demonstrated the crucial requirement of the thiol-or hydroxyl-containing residues at the two splice junctions (Cys 284 and Cys 738 as for the Vmal protozyme) and the asparagine residue immediately preceding the C-terminal junction (Asn 737 ).…”
Section: Introductionmentioning
confidence: 99%